The Influence of Adversity Quotient, Self-Efficacy, and Self-Regulated Learning on Mathematical Critical Thinking Ability of State Junior High School Students in Batam City - Br Hombing, Angelina Siswaty; Dahlan, Jarnawi A; Noviyanti, Mery; Susilowati, Erlina ayu (Jurnal Sains Sosio Humaniora, 2025)
This study investigates the critical thinking skills of ninth-grade students in public junior high schools across Batam City, specifically examining the individual and collective influences of Adversity Quotient, Self-Efficacy, and Self-Regulated Learning. Employing a quantitative cross-sectional correlational survey design, the research sampled 347 students selected via probability sampling. Data were gathered through structured questionnaires and critical thinking assessments. The results indicated that while SE exerts a positive and significant impact on critical thinking (t = 2.379 > 1.960; p < 0.05), AQ and SRL showed no statistically significant individual influence (p > 0.05). However, simultaneous analysis revealed that AQ, SE, and SRL collectively have a significant impact on students’ mathematical critical thinking skills.